Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Dee2012

  • 4 years ago

solve for c y=cx+b

  • This Question is Closed
  1. ghass1978
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    y=cx+b=>y-b=cx=>c=(y-b)/x

  2. Inopeki
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Try it yourself first

  3. Inopeki
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    y=cx+b y/x=c+b y/x+b=c But i dont know, your gonna have to think for yourself ;)

  4. across
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    @Inopeki: In your second step, you divided only the LHS by x and forgot to do the same for the RHS.

  5. across
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    (fully)

  6. Inopeki
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Oh right :/ Im gonna have to brush up on these skills :( y=cx+b y/x=c+b/x y+b/x=c ?

  7. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy